Calixarene based nanocomposite materials for high performance supercapacitor electrode - Waghmode, Babasaheb J.; Soni, Roby; Patil, Kashinath Rangu; Malkhede, Dipalee D. (New Journal of Chemistry, 2017)
A functionalised calixarene {4-Sulphatocalix [6] arene Hydrate (SC6)} stabilises MoS2/partially reduced graphene oxide (rGO) nanosheet. Such stabilised SC6-rGO/SC6-MoS2 and SC6 doped polyaniline (PANI) together forms a nanocomposite hybrid material for supercapacitor electrode. It was fabricated by an in situ polymerization method. Transmission electron microscopy (TEM) results suggest that PANI nanostructures grow homogeneously onto the surfaces of SC6 functionalised MoS2. Calixarene acts as a dopant for PANI as well as a stabiliser for the 2D nanosheets of rGO/MoS2. The characterisation of composites together with basic components was done by using various techniques namely, solid-state FT-IRspectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical performance was analysed by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectrometry (EIS). It was found that the SC6 functionalised MoS2 and SC6 doped PANI formed a uniform nanocomposite. The synthesised composites show high specific capacitance (691 F/g) and good cycling stability during the charge-discharge process when used as supercapacitor electrodes. The improvement in electrochemical performance of composites is assigned to synergistic effect of SC6 stabilised MoS2 and doped PANI. Our investigation highlighted the importance of use of calixarene in composites for above stated supercapacitor performance. The role of calixarene in the present study opens a way for the application of alike materials in the composite supercapacitors for energy storage applications.

Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction